Le Sacre du stock - Paul Landauer (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the field of architecture, as in most activity sectors in the contemporary western world, the functional part of storage remains invisible. Everywhere the just in time performance prevails. Granaries and warehouses have been replaced by sites dedicated to global chain supply. Sales areas have invaded the store reserves. Housing units are suffering from a reduction of shelves and closets. The transparency of the offices « open spaces » extends to the heart of the buildings. However, the architecture of storage resists. As the « break-through of the repressed », it spills back into our homes; it invites itself in all the actions that advocate recycling and resilience; it becomes a power issue in order to regain production autonomy; and arises among the most acute features of the hyper-industrial society such as data centers. Storage facilities, yesterday depreciated and today abandoned, could well take their revenge and (re) become the matrices of the territory of tomorrow. The architecture of storage would then regain the aura that has been his in a large number of pre-modern civilizations; an architecture of which Bernard Rudofsky, in his 1964 exhibition and book « Architecture Without Architects », has revealed the capacity to respond to four essential human aspirations: the need for monument, the search of a balance between nomadism and sedentary, the ability to cope with risks and the propensity for common projects.